Analisis produktivitas produced water pump menggunakan metode OEE dan FMEA - Felisah, Andi Ratu; Uloli, Hendra; Lahay, Idham Halid (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Produced Water is water that is produced from wells along with oil during the production process. Produced water contains soluble and insoluble oil/organics, dissolved solids, and various chemicals used in the production process. The Produced Water Pump functions to push water from the tank to the injection well which is flowed through pipes. The purpose of this study is to determine the productivity of the product water pump using the Overall Equipment Effectiveness (OEE) method which obtained the results at a performance value of 82% where this value did not reach the maximum OEE standard so that further action will be taken immediately in order to get improvements using the Failure Mode and Effect Analysis (FMEA) method with proposed improvements Providing additional training on the importance of routine maintenance and the impact of negligence, Implementing an objective performance appraisal system, Asking workers to make reports after completing maintenance tasks so that workers can find out the history of previous machine maintenance.